Effect of processing condition on properties of polylactic acid parts obtained by foam injection molding. (September 2017) - Volpe, Valentina; Pantani, Roberto
Foam injection molding is a processing technology particularly interesting for biodegradable polymers, which present a very narrow processing window, with the suitable processing temperatures close to the degradation conditions. The addition of a physical blowing agent, besides decreasing the final part weight, reduces both the viscosity and the glass transition temperature of the polymer melt, allowing the processability of these materials at lower temperatures. In this work, structural foams of polylactic acid with nitrogen as physical blowing agent were obtained by foam injection molding. In particular, the effects of back pressure, namely the pressure imposed inside of the cylinder when the screw is returning back to prepare a new amount of material to be injected, and of the injection flow rate on foaming and mechanical properties of the molded parts was assessed. It was found that the samples molded adopting a higher injection flow rate are shorter than those injected at lower flow rate, and this result was ascribed to the large compressibility of the injected shot. As far as the mechanical properties of the foamed parts, it was found that the modulus decreases with decreasing density. However, the density reduction is not the only significant parameter, but also the morphology of the foams should be taken into account in order to justify the differences between tensile and flexural modulus.